Ukrainian E-commerce Attractiveness: Challenges and Perspectives - Zatonatska, Tetiana; Kornieieva, Tetiana (Ekonomika, 2016)
E-commerce is now more than just a trend or innovation. Eastern Europe is one of the most attractive e-commerce destinations. In this article we will talk about peculiarities, principles, main trends and attractiveness of e-commerce market in Ukraine. E-commerce is a relatively new business activity in Ukraine, which is experiencing rapid growth. E-commerce has reached virtually all business spheres today, with all possible types of goods and services being sold through the Internet, from cars and computers to consulting and legal services. Investment attractiveness of e-commerce should be particularly emphasized; considering the fact that in other European countries e-commerce accounts for 15-30% of all retail transactions, the Ukrainian e-commerce market has inexhaustible growth potential.
Keywords: e-commerce; market orientation; economic value; innovations; investment attractiveness; information technologies; information society and communications